2011
DOI: 10.1038/leu.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

The surface molecule signature of primary human acute myeloid leukemia (AML) cells is highly associated with NPM1 mutation status

Abstract: ReferencesThe surface molecule signature of primary human acute myeloid leukemia (AML) cells is highly associated with NPM1 mutation status Leukemia (2012) 26, 557-559; doi:10.1038/leu.2011 published online 9 September 2011 Even though human acute myeloid leukemia (AML) is characterized by an expansion of malignant myeloblasts, these immature leukemic cells can show signs of differentiation both by morphological examination and by flow-cytometric analysis of membrane molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 8 publications
8
19
0
Order By: Relevance
“…1). FLT3 -ITD was reported not to be associated with CD34 expression by Tsykunova et al [7]. Contrarily, as shown previously [6,16,17] and in the present study, significantly low CD34 antigen expression was observed in patients with FLT3 -ITD; no correlation could be observed between FLT3 -ITD and monocytic morphology in those patients without CD34 expression.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…1). FLT3 -ITD was reported not to be associated with CD34 expression by Tsykunova et al [7]. Contrarily, as shown previously [6,16,17] and in the present study, significantly low CD34 antigen expression was observed in patients with FLT3 -ITD; no correlation could be observed between FLT3 -ITD and monocytic morphology in those patients without CD34 expression.…”
Section: Discussionsupporting
confidence: 67%
“…Tsykunova et al [7] have classified AML patients into 4 subsets according to CD34, HLA-DR and CD33 expression levels with the J-Express analysis suite [7]. However, in this study, CD33 expression levels were almost the same in all cluster II patients (CD34 high ); further, we were able to divide patients into 4 subgroups according to CD34, HLA-DR and CD11c expression levels (fig.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations